β-lactam and fluoroquinolone resistance in Enterobacteriaceae from imported and locally-produced chicken in Mozambique - Sara Lino Faife; Tomas Zimba; John Osei Sekyere; Usha Govinden; Hafizah Yusuf Chenia; Gunnar Skov Simonsen; Arnfinn Sundsfjord; Sabiha Yusuf Essack (Journal of Infection in Developing Countries)
Introduction: Plasmid-mediated resistance to β-lactam and fluoroquinolone antibiotics was investigated in Enterobacteriaceae isolated from retailed frozen chickens from Brazil, South Africa and Mozambique.